An evaluation of educational supervision from the perspective of critical theory Eleştirel kuram perspektifinden eğitim denetimine ilişkin bir değerlendirme - Kesik, Fatma; Aksu, Ali (Journal of Human Sciences, 2015)
This study aims to take the educational supervisors’ ideas on the process of supervision and their roles from the critical theory perspective. In this study designed with survey method, data were collected through semi structured interview forms and evaluated with content analysis. The working group of the study is ten education supervisors working in Manisa. As a result of the study, it was found that supervisors mostly delivered positive opinions in such dimensions of supervision as democratic, individual differences, communication, human relations; they adopted an ideal supervisory practice and reflected that to the process; they considered the supervision process as an interdisciplinary field and discussed it in terms of its relationship with society and culture, economy, and politics and lastly they delivered positive opinions about the role of curriculum and technology as the tools of education and teaching. However it was determined that although the supervisors generally adopt an inclusive attitude in terms of democratic and pluralism, they have some kind of prejudices and has reflected this to their expressions; the relationships of supervision with society, culture, economy and politics haven’t been so comprehensive and remained at a micro level and lastly they didn’t deliver critical opinions on the role of curriculum and technology, they discussed it just in terms of constructivist theory. Özet Bu araştırma il eğitim denetmenlerinin mevcut denetim sürecine ve denetmenlik rollerine ilişkin görüşlerini eleştirel kuram perspektifinden ele almayı amaçlamaktadır. Tarama modelinde tasarımlanan bu çalışmada yarı yapılandırılmış görüşme formu aracılığıyla veriler toplanmış ve betimsel analiz kullanılarak değerlendirilmiştir. Araştırmanın çalışma grubunu Manisa ilinde görev yapmakta olan 10 il eğitim denetmeni oluşturmaktadır. Araştırma sonucunda, denetmenlerin genel olarak denetimin önemli unsurları olan demokratiklik, bireysel farklılıklar, iletişim, insan ilişkileri boyutlarında olumlu görüş belirtikleri ve ideal bir denetim sürecini benimsedikleri ve bunu sürece yansıttıkları; denetimi disiplinlerarası bir alan olarak gördükleri ve toplum, ekonomi, politika ile ilişkileri bağlamında ele aldıkları ve müfredat ve teknolojinin öğretim sürecindeki rolüne ilişkin genelde olumlu görüş bildirdikleri ortaya çıkmıştır. Bununla beraber, denetmenlerin demokratiklik ve çoğulculuk bağlamında kapsayıcı bir tutumu benimsemelerine rağmen, temelde birtakım önyargılara sahip oldukları ve bunu ifadelerine yansıttıkları, toplum-ekonomi-ve politika ilişkisi bağlamında kurulan ilişkilerin daha mikro düzeyde kaldığı ve öğretimde müfredat ve teknolojinin rolüne ilişkin eleştirel görüşler sunmadıkları, bunları sadece yapılandırmacılık yaklaşımı bağlamında ele aldıkları da bu araştırmayla ortaya çıkan diğer sonuçlar arasındadır.